Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Corrigendum to “Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater” [Bioresour. Technol. 459 (2026) 135175] - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Berberine inhibits ISG15 and pyroptosis to attenuate diabetic kidney disease inflammation and fibrosis - Lingzhi Huang; Qinqin Chen; Xiaoxiao Liu; Liuqing Wang; Xingyue Liao; Siming Yuan; Liqin Tang (Apoptosis, 2026)

Ultrasonic-enzymatic synergistic extraction of Ophiopogon japonicus polysaccharides: Structural characterization, in vitro hypoglycemic activity, and regulatory mechanism on human gut microbiota - Junlin Wu; Meng Wang; Yutong Liao; Sijie Huang; Xincheng Ye; Fengchuan Ma; Siming Zhu; Yunping Peng; Dan Xu (Food Bioscience, 2026)

Okadaic acid induces oxidative stress and immunotoxicity in zebrafish: involvement of the p53 pathway and behavioral alterations - Duo Chen; Siming Pan; Jiapeng Wang; Zhenlu Li; Chenhuan Dong; Yuanxin Liang; Yilin Huang; Youqiang Chen; Ting Xue; Chentao Lin (Fish & Shellfish Immunology, 2026)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Change detection in optical and SAR images by integrating fine-grained feature extraction and contextual transformation - Man Zhang; Liang Huang; Bohui Tang; Tonggen Yang; Siming Pu (Advances in Space Research, 2025)

Benzimidazole-containing polyimide-based sensors for sequential detection of fluoride ions and water content in organic solvents - Manyu Lian; Siming Liang; Leilei Yuan; Hao Ding; Guotao Huang; Liyong Tian; Ningbo Yi; Yangfan Zhang; Qinghua Wu; Longfei Fan; Feng Gan; Yancheng Wu (Journal of Environmental Chemical Engineering, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Swelling than diffusion behavior of starch under protein crowding conditions affects the texture of the protein/starch blend gels - Xuxu Li; Mingcong Fan; Qilin Huang; Siming Zhao; Shanbai Xiong; Dapeng Li (Food Hydrocolloids, 2025)

Studies of the binding mechanism between liquid smoke from tea tree branches and proteins in dry-cured tenderloin using 4D-DIA proteomics, synergistic multispectral analysis, and molecular docking techniques - Yanpei Huang; Siming Ren; Yuanyuan Liu; Ying Zhou; Jing Wan; Linggao Liu; Qiujin Zhu (Food Chemistry, 2025)

Characteristics of Dissolved Inorganic Carbon (DIC) in the Western Coast of the Taiwan Strait Using a Shipboard Measurement - Jiehua Hu; Jinpei Yan; Hang Yang; Siming Huang; Siying Dai; Xiaoke Zhang; Shanshan Wang; Shuhui Zhao (Journal of Marine Science and Engineering, 2024)
An online dissolved inorganic carbon (DIC) monitoring system was produced to achieve high spatial and temporal resolution in DIC data from the western Taiwan Strait (WTS) during the summer. Surface seawater DIC, salinity, dissolved organic carbon (DOC), Chl-a, and NO3− samples were collected, as well as the vertical profiles of DIC, to understand DIC variations in the WTS. The results showed that the range of DIC levels in the surface seawater from the WTS was from 1.68 to 2.21 mmol/L (Mmol), with an average of 1.93 ± 0.19 Mmol, which was consistent with the sampling results using titration determination, with an average of 1.98 ± 0.12 Mmol. A high correlation (R2 = 0.96) was presented between the online monitoring and sampling detection of DIC, indicating that DIC could be measured with high accuracy using the online monitoring system. The spatial distribution of DIC was similar to that of salinity, but it was different from that of DOC and Chl-a. The DIC concentration positively correlated with salinity (R2 = 0.51) and presented a negative correlation (R2 = 0.92) with seawater temperature. However, the surface seawater DIC was almost independent from DOC and Chl-a in the observation sea areas. The DIC levels first increased and then decreased with the depth, with the highest DIC concentration occurring in the subsurface water at about 10 m, which was similar to the profiles of salinity and Chl-a in the northern and southern areas of the WTS. The profiles of DIC, salinity, NO3−, and Chl-a were almost independent from the water depth in the central WST. This indicated that seawater DIC in the WTS was mainly affected by seawater temperature, salinity, and the vertical mixing of sea water, but it was less impacted by TOC and Chl-a.

Microplastics alter the migration and transformation of vanadium in the riverine sediment environment - Siming Chen; Xinyue Zhang; Luyao Wang; Cuibai Chen; Jiamin Huang; Baogang Zhang (Science of The Total Environment, 2024)

Mesoporous carbon hollow spheres based sensitive SPME probes for in vivo sampling analysis of selected plant hormones in Chinese aloes - Yan Liu; Jiajia Han; Guosheng Chen; Siming Huang; Shuyao Huang; Juan Zheng; Jianqiao Xu; Fang Zhu; Gangfeng Ouyang (Analytica Chimica Acta, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Biodegradable copper peroxide decorated hollow polydopamine nanocomposite as effective chloroperoxidase delivery carrier for enhancing enzyme dynamic therapy via self-activated cascade reactions - Weiwei Wu; Yan Yang; Yu Zhang; Yina Zeng; Zhuoying Liang; Xiling Song; Yadong Huang; Wei Xue; Siming Yu (Chemical Engineering Journal, 2024)

Effect of hydrophobic sucrose esters with different fat acid composition and esterification degree on whipped cream properties - Di Zeng; Yongjian Cai; Tongxun Liu; Lihua Huang; Junwei Wang; Mouming Zhao; Siming Zhu; Qiangzhong Zhao (Food Hydrocolloids, 2024)

Study on hydrogenation of oxygenated aromatic hydrocarbons via water-gas shift reaction in a subcritical CO-H2O system - Jiale Gu; Huan Li; Wencai Peng; Di Zhu; Jiajia Chen; Shengjie Luo; Siming Liu; Wenxiang Zhao; Youqing Wu; Sheng Huang; Shiyong Wu (Fuel, 2023)

Emissions of formaldehyde and nitrogen dioxide from liquefied petroleum gas combustion - Jin Ye; Siming Shi; Tao Yu; Cong Liu; Jingguang Li; Zhen Ding; Zhijiong Huang; Hua Qian (Process Safety and Environmental Protection, 2023)

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Global DNA and protein interactomes of FLT1P1 (Fms-related tyrosine kinase 1 pseudogene 1) revealed its molecular regulatory functions associated with preeclampsia - Lu Zhao; Siming Xin; Yunfei Wu; Shaofang Huang; Kangxiang Xu; Yuqi Xu; Dong Ruan; Bingqi Wu; Dong Chen; Xiaoju He (Molecular Biology Reports, 2023)

Application of artificial step-pools in natural hazard mitigation - Kehan Huang; Wei Liu; Mengzhen Xu; Siming He; Yifei Cui; Zhaoyin Wang (CATENA, 2023)

Supplementation of Bacillus sp. DU-106 Alleviates Antibiotic-Associated Diarrhea in Association with the Regulation of Intestinal Microbiota in Mice - Darong Huang; Yanlan Chen; Hongzhu Chen; Xinyu Deng; Jianzhao Huang; Siming Lu; Pan Li; Bing Du (Probiotics and Antimicrobial Proteins, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Transcriptome-derived microsatellite markers for population diversity analysis in Archidendron clypearia (Jack) I.C. Nielsen - Dandan Li; Mei Li; Fagen Li; Qijie Weng; Changpin Zhou; Shineng Huang; Siming Gan (Molecular Biology Reports, 2021)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Characterization of a bifunctional alginate lyase as a new member of the polysaccharide lyase family 17 from a marine strain BP-2 - Guiyuan Huang; Shunhua Wen; Siming Liao; Qiaozhen Wang; Shihan Pan; Rongcan Zhang; Fu Lei; Wei Liao; Jie Feng; Shushi Huang (Biotechnology Letters, 2019)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

Up-regulation of SKIP relates to retinal ganglion cells apoptosis after optic nerve crush in vivo - Yu Wu; Fan Xu; Hui Huang; Lifei Chen; Meidan Wen; Li Jiang; Lu Lu; Li Li; Di Song; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Upregulation of Gem relates to retinal ganglion cells apoptosis after optic nerve crush in adult rats - Fan Xu; Hui Huang; Yu Wu; Lu Lu; Li Jiang; Lifei Chen; Siming Zeng; Li Li; Min Li (Journal of Molecular Histology, 2014)

Dissimilar characteristics of umbilical cord mesenchymal stem cells from donors of different ages - Sha Huang; Changjiang Feng; Yan Wu; Siming Yang; Kui Ma; Xu Wu; Xiaobing Fu (Cell and Tissue Banking, 2013)

Effects of Frequency on the Dynamic Properties of Intact Rock Samples Subjected to Cyclic Loading under Confining Pressure Conditions - Enlong Liu; Runqiu Huang; Siming He (Rock Mechanics and Rock Engineering, 2012)